Programming as learning resource in middle school - Salvador, Ricardo Pablo (2018)
In this work we study the influence, in the kinematics learning of secondary students, of the construction of a simulation using the Squeak Etoys graphical programming environment. An experimental work was carried out with two groups of students. One group used an interactive tutorial in whichthey constructed the simulation. The experiment was evaluated using a pretest posttest protocol. The results indicate an increase in students' gradesand interest in programming as a didactic resource, which encourages designing similar activities and exploring this resource in other disciplines.